PENILAIAN KINERJA MANAJER PUSAT PENDAPATAN, PUSAT BIAYA DAN PUSAT LABA PADA PT. PUPUK KALIMANTAN TIMUR - WIRA NUGRAHA, ANDRE (Jurnal Akuntansi AKUNESA, 2015)
Responsibility center is a unit led by a manager who is responsible for the activities undertaken in the units they manage. PT. Pupuk Kalimantan Timur is one of company that has a responsibility center. This study aims to assess the manager performance of revenue center, cost center, profit center. The analytical method used is descriptive analysis. The results showed that the manager performance of revenue center is good. While the manager performance of cost center and profit center showed poor results. The cost center managers should undertake an evaluation of the cost of production and operating expense so that next year corporate profits will be increase.Keywords: Revenue Center, Cost Center, Profit Center